Molybdenum and tungsten stimulate immune responses under biotic stress in Nicotiana abenthamiana infected with tomato bushy stunt virus - Serikovna, Tokasheva Dana; Zholdasbayevna, Akbassova Alya; Tukenovich, Omarov Rustem (International Journal of Innovative Research and Scientific Studies, 2024)
The present research examines how molybdenum and tungsten stimulate immune responses under biotic stress in Nicotiana abenthamiana. Plants are subjected to a wide range of environmental stressors that reduce and limit crop productivity. The primary response to any stress type is the production of reactive oxygen species (ROS) that cause oxidative stress, whose elimination by molybdoenzymes plays an active role. However, in the case of a molybdenum shortage in the soil or substrate, tungsten replaces molybdenum in the active centre of enzymes. Our study demonstrates the potential use of tungsten (W) and molybdenum (Mo) to stimulate the immune response of Nicotiana abenthamiana plants when interacting with Tomato bushy stunt virus (TBSV). The results indicate that the use of Mo and W metal salts activates the antioxidant system, particularly aldehyde oxidase (AO). Seed priming in metal solutions resulted in the appearance of the additional AO isoform. Furthermore, root length was high in the 1 mM Mo+W solution (4.05 cm, compared to 2.03 cm in the control). And seedling biomasses were significantly higher in infected plants in molybdenum and tungsten solutions at concentrations of 1 mM, 8.5 and 8.8 g, and about 7.6 g in control. The incubation of infected N. benthamiana plants in a solution of tungsten increased their resistance to TBSV. This is shown by a low level of accumulation of hydrogen peroxide (0.014), which is 23% less than the control infected plant. These results suggest the involvement of Mo and W in the mechanisms of resistance against viral infection and stimulation of the immune response of plants to biotic stress.